Pengaruh Pemahaman Teknologi Informasi, Pendapatan, dan Biaya Terhadap Penggunaan Platform Marketplace Shopee (Studi Pada Pelaku UMKM di Kabupaten Buleleng) - Kaswarina, Ni Ketut Nadia; Adiputra, Made Pradana (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the effect of information technology knowledge, income, and costs of the Shopee marketplace platform. This study is quantitative study with 156 respondents of micro SMEs in Buleleng Regency who use Shopee for online sales. The data obtained by distributing questionnaires using the Google Form service. The criteria for the selected samples were using the purposive sampling technique then calculated by the Slovin formula. The data of this study are the form of respondentsâ€™ answers as the primary data then processed using SPSS version 20. The results achieved the goals of this study in which the information technology knowledge, income, and costs have positives and significant effects on the use of the Shopee marketplace platform.Â